Application of organic fertilizer and phosphate solubilizing bacteria to increase the growth and yield of potatoes in Andisol - Agustina Erlinda Marpaung; Bina Karo; Susilawati Barus; Rina Christina Hutabarat; Rasiska Tarigan (Kultivasi, 2022)
AbstractAndisol has low phosphate (P) nutrient content due to high P fixation by allophane minerals, which affects crop production. The application of organic fertilizers and phosphate solubilizing bacteria can increase the availability of P in the soil in order to increase the production of potato plants. This study aimed to evaluate the effect of different types of organic fertilizer and phosphate solubilizing bacteria (PSB) on potato production. The research was conducted from August to November 2020 in the installation of research and assessment of agricultural technology Berastagi, Karo Regency, with an altitude of ± 1,340 m above sea level and the soil order is Andisol. The experimental design used a factorial randomized completely block design with four replications. The first factor was a different type of organic fertilizer (liquid organic fertilizer and chicken manure) and the second factor was a different type of phosphate solubilizing bacteria (PSB) {without PSB (control), Bacillus cereus, Bacillus pseudomycoides, and Bacillus amyloliquefaciens}. Results showed that chicken manure was able to increase the growth and yield of potatoes per plot. Phosphate solubilizing bacteria B. pseudomycoides could increase potato yields. The interaction of chicken manure and B. pseudomycoides was able to increase potato yield by 33.79% - 56.24% and the percentage of big tubers to 32.60% - 70.23% and decrease the grade of small tubers to 43.61% - 72.32% compared to without PSB. Phosphate solubilizing bacteria Bacillus pseudomycoides and chicken manure fertilization had the potential to be applied for increasing potato production in Andisol.Keywords: Bacillus sp, organic fertilizer, Solanum tuberosum AbstrakAndisol memiliki kandungan hara P yang rendah karena fiksasi P yang tinggi oleh mineral alofan, yang mempengaruhi produksi tanaman. Aplikasi pupuk organik dan bakteri pelarut fosfat dapat meningkatkan ketersediaan P dalam tanah untuk meningkatkan produksi tanaman kentang. Penelitian ini bertujuan untuk mendapatkan jenis pupuk organik dan bakteri pelarut fosfat (BPF) terbaik untuk meningkatkan produksi kentang pada andisol. Penelitian dilaksanakan pada bulan Agustus sampai dengan November 2020 di Instalasi Penelitian dan Pengkajian Teknologi Pertanian Berastagi Kabupaten Karo dengan ketinggian tempat ± 1.340 m dpl dan ordo tanah Andisol. Rancangan yang digunakan adalah rancangan acak kelompok faktorial dengan empat ulangan. Perlakuan yang diteliti adalah pertama jenis pupuk organik (pupuk organik cair dan kotoran ayam) dan faktor kedua jenis bakteri pelarut fosfat (PSB) {tanpa BPF (kontrol), Bacillus cereus, Bacillus pseudomycoides, dan Bacillus amyloliquefaciens}. Hasil penelitian menunjukkan bahwa jenis pupuk organik kandang ayam mampu meningkatkan pertumbuhan dan hasil tanaman kentang. Bakteri pelarut fosfat B. pseudomycoides dapat meningkatkan hasil kentang per plot. Interaksi pupuk organik kotoran ayam dan bakteri pelarut fosfat B. pseudomycoides mampu meningkatkan hasil kentang sebesar 33,81% - 56,26% dan persentase umbi besar 32,60% - 70,23% dan menurunkan persentase umbi kecil 43,61% - 72,32% dari tanpa BPF.Kata kunci: Bacillus sp, pupuk organik, Solanum tuberosum